2020
DOI: 10.3390/pharmaceutics12090854
|View full text |Cite
|
Sign up to set email alerts
|

Development of Theranostic Cationic Liposomes Designed for Image-Guided Delivery of Nucleic Acid

Abstract: Cationic liposomes have been considered as potential vectors for gene delivery thanks to their ability to transfect cells with high efficiency. Recently, the combination of diagnostic agent and therapeutic agents in the same particle to form a theranostic system has been reported. Magnetic liposomes are one of these examples. Due to the magnetic nanoparticles encapsulated in the liposomes, they can act as a drug delivery system and, at the same time, a magnetic resonance imaging contrast enhancement agent or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Ultra-magnetic liposomes (UMLs), prepared by means of the reverse-phase evaporation method, exhibited a higher magnetic nanoparticle (MNP) loading efficiency (about 100-fold), compared to the classical thin-film hydration method [ 91 ]. Do et al [ 92 ] developed nucleic acid-delivery nano-formulation systems based on magnetic cationic liposomes (MCLs), by means of reverse-phase evaporation and cosolvent sonication techniques. The new MCLs’ nano-formulation composed of the lipids DPPC, DSPC, DOPE, 18:0 PEG2000 PE, 14:0 PEG750/1000/2000 PE, and cationic lipid DMAPAP, showed high capacity and efficiency to form complexes and transfect (CT-26) cells (using the antibiotic-free pFAR4-luc plasmid), thanks to their ability to transfect cells with high efficiency.…”
Section: Conventional Methods For the Preparation Of Liposomesmentioning
confidence: 99%
“…Ultra-magnetic liposomes (UMLs), prepared by means of the reverse-phase evaporation method, exhibited a higher magnetic nanoparticle (MNP) loading efficiency (about 100-fold), compared to the classical thin-film hydration method [ 91 ]. Do et al [ 92 ] developed nucleic acid-delivery nano-formulation systems based on magnetic cationic liposomes (MCLs), by means of reverse-phase evaporation and cosolvent sonication techniques. The new MCLs’ nano-formulation composed of the lipids DPPC, DSPC, DOPE, 18:0 PEG2000 PE, 14:0 PEG750/1000/2000 PE, and cationic lipid DMAPAP, showed high capacity and efficiency to form complexes and transfect (CT-26) cells (using the antibiotic-free pFAR4-luc plasmid), thanks to their ability to transfect cells with high efficiency.…”
Section: Conventional Methods For the Preparation Of Liposomesmentioning
confidence: 99%
“…Drug release from MNPs has both a time-and concentrationdependent pattern [55,56,57,58,59,60]. Magnetic nanoparticles can be encapsulated into liposomes using the thin-film hydration method [61,62] or reverse-phase evaporation method [63,64,65]. Hydrophobic magnetic nanoparticles will be integrated into the liposome bilayer membrane, while hydrophilic magnetic nanoparticles will be integrated into the liposome core.…”
Section: Magnetic Responsivementioning
confidence: 99%
“…Focusing on this, Do et al [99] recently reported an optimized preparation of cationic magnetoliposomes for magnetic transfection of a pFAR4-luciferase plasmid to CT26 cells.…”
Section: Protein and Gene Deliverymentioning
confidence: 99%